THE Amazing Law of Influence - Duncan, King, author 652028 (Petaling Jaya, Selangor : Advantage Quest Publications, 2006)
Ten ways to change your world. If you knew you could exert a positive influence on the world, would you really do it? One person can make a difference. This reader-fiendly book looks at chaos theory-how small changes can trigger monumental transformations. Scientists have long studied the principles associated with atomic structure and behavior-that through a chain of reactions, a butterfly flapping its wings in Malibu can produce a monsoon in Malaysia months later-but its application to human behavior has been regarded merely as 'a nice idea'. But is it just that, or is it really possible to change the world, one's community, or even relationships within a family? Full of engaging anecdotes and concrete advice, The Amazing Law of Influence demonstrates the importance of each life to the human family. It goes even further than that to show how it is possible for one person to make a lasting change to family, community, and even humanity as a whole.